2017
DOI: 10.1007/s00441-017-2630-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying podocyte depletion: theoretical and practical considerations

Abstract: Podocyte depletion is a central event in the pathogenesis of many glomerular diseases. For this reason, methods to quantify podocyte depletion have become increasingly important. Here, we review currently available methods for quantifying podocyte depletion, including the analysis of glomerular cross-sections, the most important and common stereological methods and newer techniques such as whole glomerular analysis in optically cleared samples. Each method has advantages and limitations. We therefore discuss t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Why is the methodology to measure podocyte number important in this debate? [ 47 49 ] Methods that rely on the podocyte mean derived by summing podocyte number (numerator) in a fixed number of glomeruli (denominator) regardless of their degree of injury, will underestimate podocyte replacement in individual glomeruli because of the focal nature of disease in healthy aging. In the current study, we make two important observations in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Why is the methodology to measure podocyte number important in this debate? [ 47 49 ] Methods that rely on the podocyte mean derived by summing podocyte number (numerator) in a fixed number of glomeruli (denominator) regardless of their degree of injury, will underestimate podocyte replacement in individual glomeruli because of the focal nature of disease in healthy aging. In the current study, we make two important observations in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that the use of 4 μm sections, particularly when observing glomeruli, is problematic due the relatively small sampling of the ≅80 μm glomerulus (4μm = 5%), and the inherent heterogeneity in glomerular size both normally and in disease 20 . In the current study, we utilized 20 μm sections and optical sectioning by confocal microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Podocyte depletion indices were assessed by the Weibel and Gomez method 67 validated by White and Bilous 68 in the kidney. This is one of the preferred methods to determine podocyte depletion parameters when limited tissue is available 69,70 . Briefly, 1-μm-thick paraffin sections were cut and stained with anti-p57, anti-SNP, and anti-CD44 antibodies and conjugated with AF488, AF594, and AF647, respectively.…”
Section: Methodsmentioning
confidence: 99%